Prototyping Participation: 3D Printing Co-design Into Healthcare - Munn, Joshua (Auckland University of Technology, 2017)
Increasingly accessible, affordable and technically viable, 3D printing is now being used for a number of high-end healthcare applications, including orthopaedic implants, prosthetics and dentistry casting. These applications, however, are largely driven by an industry that is often not embedded within the complex environments for which it is designing, therefore potentially lacking an in-depth understanding of the end-user. In contrast, this practice-based research operated within a hospital environment and alongside healthcare professionals who possessed a practical understanding of clinical requirements and the patient experience. Using a co-design methodology, a series of problems were identified and developed in workshops. Objects were designed and printed that not only leveraged the specific properties of 3D printing – rapid, iterative, and customisable – but also worked as a tool for co-design. These 'probes' were not a forerunner of the future product, but rather vehicles for observation, reflection, interpretation, discussion and expression. Probes helped to create a bridge between the worlds of design and health, acting as a common language between the designer and the participant in order to help establish a shared understanding. This shared understanding provided a stronger foundation for the collaborative identification and development of an optimal design opportunity, suitably linking a specific clinical problem with the capabilities of technology. In this way, 3D-printed probes helped co-design interactions evolve from passive exchanges of knowledge to active relationships. These more effective co-design relationships appear to provide a more reliable model for design outcomes in results- driven environments such as hospitals.
Keywords: 3D printing; Design; Healthcare; Hospital; Additive manufacturing; Digital technologies; Co-design; Collaboration; End-users; Human-centred design; Probes; Transparency; CAD; Modeling; Shared understanding; Participatory design; 3D scanning; Parametric design